Archives & Special Collections at Curtin University Library - Wells, David; Laming, Sally (2022)
The article briefly outlines the history and vision of the John Curtin Prime Ministerial Library (JCPML) at Curtin University and provides an overview of its archival and special collections holdings. The primary focus of the JCPML is the life and times of John Curtin (1885-1945), Australia’s wartime prime minster, and by extension the Australian-US relationship, post-war reconstruction, foreign policy, social and political history, and the prime ministership as an office. Other collection areas include post-war Australian political history, women’s health, sexology, folklore in Western Australia, architecture, East Africa during the period of decolonization, and library studies. The JCPML also hosts material relating to yachtsman Jon Sanders’ solo triple circumnavigation of the world in 1986-1988, and the Elizabeth Jolley Research Collection, as well as a collection of rare books and maps.